Basic Theories and Concepts of Psychology - Baxtiyorova Umida Ulug‘bek qizi (Open Academia, 2024)
Psychology as a science is extensive and includes many theories and concepts, each of which attempts to explain various aspects of human behavior and the psyche.
Keywords: psychology; behaviorism; approach